2012
DOI: 10.1039/c2nr31402a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical functionalization on the CO2/N2 separation performance of porous graphene membranes

Abstract: The separation of CO₂ from a mixture of CO₂ and N₂ using a porous graphene membrane was investigated using molecular dynamics (MD) simulations. The effects of chemical functionalization of the graphene sheet and pore rim on the gas separation performance of porous graphene membranes were examined. It was found that chemical functionalization of the graphene sheet can increase the absorption ability of CO₂, while chemical functionalization of the pore rim can significantly improve the selectivity of CO₂ over N₂… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(162 citation statements)
references
References 39 publications
5
157
0
Order By: Relevance
“…The structures of the oil and water molecules are shown in Figure 1b. For the hydroxylated graphite system, hydroxyls are arranged uniformly on the first layer of the graphite surface to modify the graphite [20]. Figure 1c shows the local configuration of the hydroxylated graphite surface.…”
Section: Model and Methodsmentioning
confidence: 99%
“…The structures of the oil and water molecules are shown in Figure 1b. For the hydroxylated graphite system, hydroxyls are arranged uniformly on the first layer of the graphite surface to modify the graphite [20]. Figure 1c shows the local configuration of the hydroxylated graphite surface.…”
Section: Model and Methodsmentioning
confidence: 99%
“…221 Various other theoretical studies have elaborated on the use of graphene porous membranes in gas phase separation. 152,[222][223][224][225] These studies focus on the functionalization of the pores and/or changing the pore size to enhance the gas phase separation efficiency, as such synthetic methods that can produce these nanostructures are very important. An interesting theoretical study by Brockway and Schrier has shown that a graphene membrane model based on a previously synthesized graphene porous membrane can be used to separate He from natural gas.…”
Section: Gas Phase Separationmentioning
confidence: 99%
“…The authors showed that these membranes selectively lter the gas mixture by preferably adsorbing one species over the other. 152 By using DFT and molecular dynamics simulations Carrillo et al studied the adsorption of CO 2 on a Ti-graphene system with high metal coverage. 153 It was shown that the positive charge carrying Ti atoms on graphene surfaces attract negatively charged oxygen atoms towards the graphene surfaces, thereby dominating the initial repulsion of the C atom by the Ti atoms.…”
Section: Gas Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, graphene and related materials it derives are considered as excellent membrane materials in gas separation applications by its nature of single-atom thickness [4]. So far, most studies have considered an idealized, single-layer system with variations in several key parameters, such as nanopore size or chemical modification [5,6]. Zhu and his coworkers have demonstrated that C 2 N monolayer with 3.0 Å pore size showed an exceptionally high selectivity for He/Ne (Ar, CH 4 , CO 2 , N 2 , et al) in a wide range of temperature [5].…”
Section: Introductionmentioning
confidence: 99%